REIMAGINING RURAL DEVELOPMENT IN POST PANDEMIC INDIA: ROLE OF STATE AND CIVIL SOCIETY IN THE BACKDROP OF MIGRATION - Kumari, Meena; Chitalkar, Sonali; Tiwari, Vimlok (ShodhKosh: Journal of Visual and Performing Arts, 2022)
State plays a vital role in the development and progress of its citizens all around the world. Within the state people migrate from one state to another, from one region to another in search of better living conditions and livelihood. The aim of the present paper is to examine the degraded life of these peripatetic workers, specifically poor and backward among them in post pandemic India. The main question which prompted this paper is what is the relationship between the rural development and the condition of poor migrant workers in India? There are other equally relevant questions this article tries to underline such as what is the major cause of migrant hardships which triggers migration from the rural to urban areas? How is the migrant workers access to the social benefits in the ‘State of Absorption’? What is the city's approach toward the rural migrants from other parts of India? What is the responsibility of the state toward its internally migrant population in a period of crisis and emergency? Finally the paper will try to suggest a possible alternative to present the problem by linking it to Gandhi's idea of rural development?